The effect of temperature of sodium hypochlorite on fracture resistance of endodontically treated teeth – An in vitro study - Agarwal, Namrata; Nagamaheshwari, X.; Kaushik, Mamta; Soujanya, E.; Mehra, Neha; George, Alvin (Journal of conservative dentistry, 2025)
Sodium hypochlorite (NaOCl) is commonly used in endodontics for its strong antimicrobial properties, with heating enhancing its reactivity and ability to dissolve organic matter. Cryo-treated hypochlorite, however, can help reduce postendodontic pain. The chemical composition and temperature of irrigants play a key role in influencing the tooth structure's physical properties, potentially affecting treatment outcomes. The study aims to evaluate the effect of various temperatures of NaOCl which is 60°C, 45°C, 25°C, and 2°C on the fracture resistance of endodontically treated teeth. After the selection of 40 single-rooted teeth, the decoronation, and chemomechanical preparation was done, and the teeth were randomly assigned into four groups ( = 10 in each group) based on the final temperature of NaOCl. Group I at 60°C, Group II at 45°C, Group III at 2°C, and Group IV (control) at 25°C. The teeth were then tested for fracture resistance using a universal testing machine with a crosshead speed of 1 mm/min. One-way ANOVA and Tukey's tests were used. Group II (45°C) exhibited significantly higher fracture resistance compared to all other groups ( < 0.001), followed by Group III (2°C) and Group IV (25°C), whereas Group I (60°C) demonstrated the lowest fracture resistance. For optimal effectiveness, it is recommended to irrigate with NaOCl at a temperature of 45°C. This ensures enhanced antimicrobial activity. In addition, this temperature helps maintain the integrity of the endodontically treated teeth.